PENGARUH KETRAMPILAN PROSES SAINS DAN MEDIA PEMBELAJARAN ANIMASI TERHADAP HASIL BELAJAR BIOLOGI KONSEP JARINGAN TUMBUHAN SISWA KELAS XI SEMESTER GANJIL TAHUN PELAJARAN 2016-2017 DI SMAN 1 TANGGUL JEMBER - EDDY PRAYITNO (Journal of Education Technology and Inovation, 2018)
This research is to know the influence of science process skill and animation learning media to learning result. Learning outcomes in question is learning subject Biology material The concept of plant tissue. The problems studied in this research are: 1) is there any influence of science process skill to student learning result ?, 2) is there influence of animation learning media to student learning result ?, and 3) is there influence jointly between skill of science process and media of learning Animation on learning outcomes? Objectives: 1) examine the influence of science process skills on student learning outcomes. 2) the influence of learning media animation on student learning outcomes. 3) examine the mutual influence between science process skills and animation learning media on learning outcomes. The respondent of this study are students of class XI MIPA SMAN 1 Tanggul Jember Lesson 2016/2017 with the number of 120 students, the study area is determined by purposive sampling method area. This research is a quantitative research with causal design. Data collection tools use questionnaires, observations, tests and methods of documentation and interview. Valid and valid reliability tools with validity and reliability tests. The instrument analysis test uses: 1) descriptive test, 2) classical assumption test: : 1) normalitas test, 2) multikolinieritas test, 3) heterokedastisitas test, 4) autokorelasi test. Test the hypothesis by: 1) regression analysis, 2) F test, 3) t test, 4) test coefficient of determination (R2). The results showed that: 1) sig value. From the variable of science process skill to student learning result 0.000, sig conclusion. > 0,05, mean science process skill have significant effect to result of student learning, 2) sig value. Of the animated learning media variable is 0.000, sig conclusion. > 0,05, this means learning media animation have a significant effect on student learning result, 3) result of regression analysis output obtained Fcount 53,112 with sig. 0.000, because> 0,05 then there is influence together between skill of science process and media of learning animasi to result learn. Suggestions put forward so that the teachers pay attention to the skills of the science process and animation learning media to achieve better learning outcomes.